Workers' representation and labour conflict at company level: The Italian binary star in the prism of the Swedish ternary system*. Issue 1 (March 2017) - Pietrogiovanni, Vincenzo; Iossa, Andrea
This Article critically evaluates the recent trends in Italian industrial relations in order to highlight the clash between Italian constitutional principles and the autonomous development of self-regulation as for the relationship between representation, conflict and collective agreement. By conducting a comparative analysis with the Swedish model, the article argues that the constitutional principles of the Italian system of industrial relations conceive the collective agreement as a contingent element in the relationship between representation and conflict, whereas the Fiat case (2010) and the latest interconfederal agreements (2013 and 2014) place it at the centre of such a relationship. The Swedish model, instead, regards the collective agreement as a central mechanism through which the signatory trade union trades social peace with privileged rights of representation in the workplace. Through the prism of the Swedish model, the article suggests that Italian industrial relations are turning towards a restrictive system centred on the collective agreement, in which however the obligation of social peace is not exchanged with any strengthening of union representation in the workplace.